By the stroke of a pen : an evaluation of the Cape Times and Die Burger’s portrayal of racial reclassification from 1980-1990 - Chalmers, Brittany Inge (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.